Răspuns :
a) (x - 1)² - 2(x + 3) = 5x - (x - 2) + x²
x² - 2x + 1 - 2x - 6 - 5x + x - 2 - x² = 0
- 8x - 7 = 0
x = - 7/8
b) (x + 2)² + 2(x² - 1) = 3x² - (x + 2)
x² + 4x + 4 + 2x² - 2 - 3x² + x + 2 = 0
5x + 4 = 0
x = - 4/5
c) x² - 4 + (x - 3)² = 2x² - (-x + 1)
x² - 4 + x² - 6x + 9 - 2x² - x + 1 = 0
- 7x + 6 = 0
x = 6/7
2.
a) - 2x + 6 - 4x - 8 + x = - 1
- 5x = 2 - 1
x = - 1/5
b) x - 3x - 3 + 2x + 3x = 0
3x = 3
x = 1
c) 2x + x - 1 + x = 6
4x = 7
x = 7/4
x² - 2x + 1 - 2x - 6 - 5x + x - 2 - x² = 0
- 8x - 7 = 0
x = - 7/8
b) (x + 2)² + 2(x² - 1) = 3x² - (x + 2)
x² + 4x + 4 + 2x² - 2 - 3x² + x + 2 = 0
5x + 4 = 0
x = - 4/5
c) x² - 4 + (x - 3)² = 2x² - (-x + 1)
x² - 4 + x² - 6x + 9 - 2x² - x + 1 = 0
- 7x + 6 = 0
x = 6/7
2.
a) - 2x + 6 - 4x - 8 + x = - 1
- 5x = 2 - 1
x = - 1/5
b) x - 3x - 3 + 2x + 3x = 0
3x = 3
x = 1
c) 2x + x - 1 + x = 6
4x = 7
x = 7/4